PENGEMBANGAN KEWIRAUSAHAAN DENGAN MENCIPTAKAN WIRAUSAHA BARU DAN MANDIRI - Widayati, Enny; Yunaz, Haswan; Rambe, Tagor; Siregar, B. Wishman; Fauzi, Achmad; Romli, Romli (FEB Universitas Sam Ratulangi Manado, 2019)
Ideas for starting a business or business begins with observing the environment. Usually new ideas emerge as a result of the process of one's interaction with the environment. Therefore the choice of environment and form of business must be observed carefully. Here an entrepreneur must be observant in assessing and handling various problems and opportunities that arise in the environment. For example, there are two prospective entrepreneurs coming to a community somewhere. These two people found the same fact that everyone in the community did not wear shoes or sandals. After studying and identifying the cause, prospective entrepreneur A concludes there is no point in starting a shoe business here because A believes that the behavior of people who are not shoes or sandals are ingrained and cannot be changed.Keywords:Â Ideas, Observing, Forms of Business